Treatment and Genotypic Characteristics of Patients with Rheumatoid Arthritis - Norbutoev Olimjon; Akhmedov Khalmurad; Abdurakhmanova Nargiza; Turaev Ikhtiyor (BIO Web of Conferences)
Rheumatoid arthritis (RA) is a significant problem in modern rheumatology, with many patients failing to achieve remission despite the availability of new treatments. A key approach to addressing this problem is pharmacogenetics, which tailors treatments based on genetic characteristics. This study focuses on genotyping of MDR1 gene polymorphisms, specifically the C1236T, G2677T, and C3435T isoforms, in patients with RA. The results showed a significant correlation between the C3435T polymorphism and the duration of remission as well as disease activity. Carriers of the TT genotype experienced longer remissions, while patients with the CC genotype exhibited resistance to methotrexate. Based on the genotyping results, individualized treatment regimens were developed, with a focus on methotrexate monotherapy for patients with the TT genotype and alternative treatments for CC carriers. These results highlight the potential of pharmacogenetics to optimize RA treatment and reduce disease activity, leading to better patient outcomes. Further research is recommended to improve personalized RA therapy.